Pengembangan Iklim Investasi Daerah - Sopandi, Andi; Nazmulmunir, Nandang (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2012)
The dynamics of regional economy development that all this time is moved by domestic consumption needs to be pushed by investment and export. For thatreason, conducive investment climate is needed. It is a climate that encourages someone to do investment with cost and risk as low as possible and produces high and long term profit. There are some factors which influence the investment, namely politic and social stability, base infrastructure condition, financing sector, labor market, regulation, taxation, bureaucracy, corruption, consistency and policy assurance.